Development or decline of marketing - systematic considerations - Sobotkiewicz, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
The article is an attempt to answer the question: Is the influence of marketing in the organization increasing or decreasing? In the search for answers to this question, changes that took place in marketing over the past twenty years haves been analyzed. Particular attention and a lot of space was devoted to the evolution of the marketing function and marketing management concept in the practice of business entities. The considerations undertaken in the study allowed, on the one hand, indicatine the weakening of the importance of the marketing function in favour of the marketing concept of management, and on the other hand determinine their contemporary role in business practice.
Keywords: marketing function; marketing management concept; marketing development directions; funkcja marketingowa; marketingowa koncepcja zarządzania; kierunki rozwoju marketingu